Macrophyte vegetation of artificia l water reservoirs in the Krupinská planina Mts., including the first record of Potametum acutifolii from Slovakia - Hrivnák, Richard (Hacquetia, 2015)
Research of macrophyte vegetation of the artificial water reservoirs was carried out during the vegetation season of 2008 in the Krupinská planina Mts. (southern part of central Slovakia). Twenty-one reservoirs were studied and twenty plant communities from the Lemnetea, Potametea and Phragmito-Magnocaricetea classes were found. Potametum acutifolii is a new aquatic community for the territory of Slovakia that was found in the reservoir near Hrušov village in intermediately deep, slightly alkaline water with a relatively low content of soluble mineral matters, a high water transparency and a silt-clay sediment on the bottom. Moisture was the main environmental gradient of the studied vegetation explained by Ellenberg′s indicator values. Species richness was significantly negatively correlated with water depth. The correlation between the area of reservoirs and the number of detected plant communities was weak and non-significant. Changes of macrophyte vegetation were studied on the case of three reservoirs. Detected changes were caused mainly by human activities or water level fluctuations within the studied period.